2017
DOI: 10.1021/acs.biomac.7b01048
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogelation of a Naphthalene Diimide Appended Peptide Amphiphile and Its Application in Cell Imaging and Intracellular pH Sensing

Abstract: This study reports the self-assembly and application of a naphthalene diimide (NDI)-appended peptide amphiphile (PA). H-bonding among the peptide moiety in conjunction with π-stacking between NDI and hydrophobic interactions within the alkyl chain are the major driving forces behind the stepwise aggregation of the PA to form hydrogels. The PA produced efficient self-assemblies in water, forming a nanofibrous network that further formed a self-supportive hydrogel. The molecule followed a three-step self-assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 62 publications
1
48
0
Order By: Relevance
“…Similar studies were performed with two of our previously reported hydrogels. 25,26 However, in both cases, the hydrogels get dissolved in bulk H 2 O/D 2 O and all the H 2 O molecules were found in the NMR samples. These results demonstrate that the self-assembly creates a system where both the gel-network and the water of gelation are inaccessible to the surrounding environment.…”
Section: Resultsmentioning
confidence: 98%
“…Similar studies were performed with two of our previously reported hydrogels. 25,26 However, in both cases, the hydrogels get dissolved in bulk H 2 O/D 2 O and all the H 2 O molecules were found in the NMR samples. These results demonstrate that the self-assembly creates a system where both the gel-network and the water of gelation are inaccessible to the surrounding environment.…”
Section: Resultsmentioning
confidence: 98%
“…Peptide-Based Smart Therapeutic Hydrogels NDI in case of 46) to provide additional stability to the aggregates (Singha et al, 2017). Recently, we have demonstrated the combination of charge transfer (CT) and cation-π interactions between two molecules that lead to the formation of a self-healing hydrogel.…”
Section: Das and Dasmentioning
confidence: 99%
“…The MSCs labeling results demonstrated that the peptide‐modified SPIONs could improve the targeting efficiency and the rate of positive labeling by up to 95%. Das and co‐workers used a fluorescent naphthalene diimide as a linker to conjugate the hydrophobic C 6 H 13 ‐alkyl chain and the hydrophilic GKRGDS peptide. The resultant peptide amphiphile could self‐assemble into hydrogels through a three‐step self‐assembly mechanism.…”
Section: Self‐assembled Peptide‐based Nanoprobes For Cell Imagingmentioning
confidence: 99%